The Culture of Pain - Morris David B (University Of California Press, 1991)
A deeper understanding of our common afflictions, our humanity, and our ennobling struggle for transcendence. Figures, Acknowledgements, Introduction, Living Pain: Mystery or Puzzle?, The Meanings of Pain, An Invisible Epidemic, The Pain of Comedy, Hysteria and Pain and Gender, Visionary Pain and the Politics of Suffering, Pain is Always in Your Head, The Uses of Pain, Painful Pleasures: Beauty and Affliction, Sex and Pain and the Marquis de Sade, Tragic Pain, The Future of Pain, Notes, Index.